Building Reproductive Health Awareness Through Digital Approach for Adolescents in the Social Media Era (Oshada, 2025)
Lack of awareness and education on reproductive health among adolescents is a significant challenge, especially due to limited accurate information and strong social stigma. Social media and digital technology offer great potential in improving adolescents’ understanding of reproductive health through wider access to information and engaging educational formats. Platforms such as Instagram, TikTok, and YouTube have become primary sources for adolescents in seeking information related to sexual and reproductive health. However, the main problem that arises is the rampant misinformation that can form erroneous understandings. Low digital literacy makes it difficult for many adolescents to distinguish between valid information and hoaxes. To overcome this, an evidence-based approach is needed by involving health workers in content production and stricter regulation of information on social media. In addition, the development of interactive health applications can be an effective solution to provide access to credible information and create a safe discussion space for adolescents. Collaboration between the government, health institutions, and social media platforms is an important step in increasing the validity of the information disseminated. With the right strategy, social media can be an effective educational tool in building awareness of reproductive health among adolescents.